Implementasi Hasil Pelatihan Perawatan dan Pengelolaan Pasca Panen Jamur Tiram Putih - Nunik Ratnaningtyas; Nuraeni Ekowati; Dian Bhagawati; Sri Lestari (Asosiasi Dosen Akuntansi Indonesia, 2020)
Training on the care and post-harvest management of oyster mushrooms has been carried out for the community in Gandatapa Village to strengthen the program of activities of mothers and youth groups at Grumbul Sirapan Kidul. This effort was made to increase the knowledge and skills of the target audience, which at the same time was a means of supplementing income during the impact of Covid-19. The training was conducted in a participatory manner through tutorials, practice, and making demonstration plots. The activity's implementation stages are preparation, training on white oyster mushroom cultivation, evaluation, and program sustainability. Analysis of the data and information obtained was descriptively based on the target audience's activities in participating in the training and managing the demonstration plot. The results of the activity show that the movement can run well and smoothly. Individually, the target audience has increased their knowledge and skills with oyster mushroom cultivation. The demonstration plot results show that the target audience can care for and manage it, but the production of mushrooms after the first harvest is not optimal. There is still a need for continuous technical assistance to optimize production.